(untitled) (Research, Society and Development, 2020)
Potentially toxic elements can be considered serious environmental contaminants, as they do not degrade and have a cumulative effect on the environment and on the organism of several species. Considering that contamination by metals may be associated with the decline of waterfowl, the objective of this work was to perform a quantitative temporal analysis, through a scientometric approach on the contamination and possible decline of waterfowl that inhabit areas potentially contaminated by metals. 239 publications were found indexed in the two databases analyzed, with 218 publications in the Web of Science database, with a representation of (91.21%) and 21 publications (8.79%) in the Scopus database. The analyzed works studied 25 families and 66 bird species that had at least one organ / tissue / structure (liver, feces, stomach bolus, blood, lung, brain heart feather, bones, nail, muscle tissue, eggs) contaminated by at least one of the 18 metals found in the analyzed articles (Hg, Pb, Zn, Cu, Cd, Fe, Mg, Ca, Mn, Sr, As, Ni, Sc, Al, Ag, Co, Cr) and MeHg which is the organic form of Hg. The results of the analyzed researches indicated that the studied metals, can compromise the survival, foraging capacity of birds in their natural environment, also impairing the morphological development, which could decrease the possibility of reproductive success, and, therefore, contribute to the decline of water bird populations around the world.